ARTIFICIAL INTELLIGENCE IN THE ELECTRIC VEHICLE ECOSYSTEM: ADOPTION; IMPACT; AND FUTURE PROSPECT - Fadillah, Jihan Trie (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Artificial Intelligence (AI) has been around since 1940, namely the first digital computer called Atanasoff Berry Computer (ABC) which aroused the enthusiasm of scientists to develop the idea of making an "electronic brain" or hiding electronic devices in the human brain . With Artificial Intelligence (AI) that can work efficiently, of course, work can be done more easily. The purpose of writing this scientific paper is to explain the use of Artificial Intelligence (AI) in the automotive industry which can make it easier for humans in the future. The method taken by the author is through observations obtained from browsing (searching) through the internet, quoting from various written sources and books that match the theme. Artificial Intelligence (AI) is created in machines and made capable of applying them in real life. Artificial Intelligence (AI) embedded in the steering wheel for self-driving cars complements the driver’s abilities when it comes to driving. So that the driver can drive more safely. In the automotive industry, Artificial Intelligence (AI) can be implemented to find a balance point between reactive maintenance (risk of failure) and preventive maintenance (can incur high costs) which uses sensors to track equipment conditions and analyze data on an ongoing basis. An example of the application of Artificial Intelligence (AI) in automotive is in its manufacture by carrying out monitoring processes, errors, downtime and optimizing production operations.